A Psychiatrist’s Grief – The Neglected Suicide Survivor: A Brief Article - NUR IWANA, ABDUL TAIB; Muhammad Hanif, Abd Latif; Nurazah, Ismail; Johari, Khamis; Ravivarma Rao, Panirselvam; Tuti Iryani, Mohd Daud; Abdul Hakem, Zahari (Wolters Kluwer - Medknow, 2024)
One of the most impactful griefs that any psychiatrist could experience throughout their professional career is the loss of patient from suicide. However, the treating psychiatrists were often overlooked from receiving any form of support dealing with the loss. As grief following a patient’s suicide is still underexplored among Malaysian psychiatrists, the purpose of this article is to review current literature on suicide grief experience among psychiatrists, its impact on the psychiatrist’s clinical practice, and to identify potential grief support measures that can be implemented for psychiatrists. A literature search was conducted on the experience of losing patient by suicide among psychiatrists, clinicians, and other mental health providers. Studies found that the high percentage of psychiatrists experiencing patient’s suicide is consistent globally. Patient’s suicide led to poor psychological well‑being with higher levels of trauma symptoms and affected the psychiatrist’s clinical practice. Multiple factors associated with the impact of the loss among psychiatrists were reported. Globally, few postvention protocols and guidelines have been created to navigate the challenging impacts of a patient’s suicide. Confidentiality concerns, disenfranchised grieving, negative responses from colleagues, and stigma around suicide often serve as barriers for psychiatrists to seek help. Posttraumatic growth was reported among psychiatrist‑survivors following the trauma. Patient’s suicide loss can negatively affect psychiatrists, but adequate support can lead to posttraumatic growth. It is recommended to first investigate the experience of grieving among psychiatrists in Malaysia and then establish a local guideline or postvention program for psychiatrist survivors that suit the sociocultural context.